TH8.6 Thoracic sarcoma: three-year data from a tertiary referral centre. (9th August 2022) - Saifuddin, Sarah; Hoppe, Solveig; Williams, Matthew; Cosker, Thomas; Stavroulias, Dionisios; Di Chiara, Francesco
Abstract: Aims: The rarity of thoracic sarcomas leads to challenges in their diagnosis and evidence-based management. We aim to investigate the management and outcomes of primary thoracic sarcoma patients under the care of our tertiary centre Sarcoma Service over a three-year period. Methods: Data of all thoracic sarcoma patients discussed at the tertiary centre multidisciplinary meetings from 2017–2019 were collected from the local electronic database. Results: 65 patients met the inclusion criteria. The most common histological subtypes were chondrosarcomas and spindle cell sarcomas. 60% of cases were high-grade sarcomas. 14 out of 19 deaths occurred in patients with high grade sarcomas (p=0.0586). 78.3% of patients underwent surgical resection, with 35.4% undergoing surgical resection as their sole treatment modality. Surgical intervention was associated with a statistically significant improvement in survival (p < 0.0001*). Clear marginal status was associated with better survival outcomes (p = 0.026*). Local recurrence was seen in 15 cases, and 93.3% of these were in high-grade sarcomas. There was no association between recurrence and marginal status. 8 of the 15 cases with recurrence received surgical intervention for the recurrence. 4 of the cases with recurrence passed away within the study time frame. Conclusion: Primary resection should remain the gold standard for treatment of thoracic sarcomas due to its significant improvement in survival. Variability between outcomes and overall survival is likely multifactorial – diversity of histological subtypes, predominance of high-grade sarcomas, and a wide range of age at diagnosis. Prospectively maintained databases and cross-centre collaboration would be beneficial for future study in thoracic sarcomas.